MEMBANGUN KARAKTER RELIGIUS MELALUI PEMBUDAYAAN AGAMA DAN PEMBELAJARAN AL-QUR'AN HADIS DI LEMBAGA PENDIDIKAN - Nailul Muna; Asmira Laila; Anisa Nurul Fadhilah; Muhammad Fauzan; Sumiarti; Hamzah Irfanda (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
The formation of students' religious character in the era of globalization requires a comprehensive approach that integrates the cultivation of religious values in school life and deepens understanding of Islamic teachings through the study of the Qur'an and Hadith.This literature review analyzes strategies for developing a religious culture in schools and effective methods of teaching the Qur'an and Hadith at the high school/vocational school level. The results show that religious culture is formed through the internalization of values involving all components of the school, including routine religious activities, teacher role models, and the integration of religious values into learning.Effective Al-Qur'an Hadith learning must be tailored to the characteristics of critically thinking teenagers, including in-depth tajwid, Ulumul Qur'an, Ulumul Hadith, thematic interpretation, and contextualization of verses and hadiths with modern life. A combination of structural, active, technology-based, and project-based approaches has been proven to improve students' understanding and practice. The synergy between religious culture and quality Al-Qur'an Hadith learning produces a generation that is faithful, knowledgeable, noble, and ready to face global challenges.